Tata Kelola Pelayanan Pengelolaan Sampah di Kota Bandar Lampung - Pamungkas, Pandu; Pangestu, Aji (Policy, Law and Political Research Center, 2026)
This study aims to analyse the role of the Bandar Lampung City Environment Agency (DLH) in the implementation of waste management services and to identify the challenges and innovations developed in supporting sustainable waste management. This study uses a descriptive qualitative approach with a literature review method, through a review of policy documents, local regulations, DLH performance reports, and secondary data related to waste management. The results of the study show that although operational waste management achievements have improved, the annual growth in waste volume has not been fully offset by infrastructure capacity, funding, and the effectiveness of the management system. Low community participation in waste sorting at source and dependence on conventional management patterns remain major obstacles.DLH has developed various innovative efforts, such as the Postalinga programme, strengthening waste banks, increasing human resource capacity, and cross-sector collaboration with the government, the private sector, and the community. These innovations have made a positive contribution to waste reduction efforts, particularly organic waste, but still require expansion in scope and consistency in implementation. With strengthened governance, sustainable financing, and increased public awareness, Bandar Lampung City has great potential to realise an efficient, environmentally friendly, and sustainable waste management service system.